2013
DOI: 10.1177/1367006913507005
|View full text |Cite
|
Sign up to set email alerts
|

Applications of stalling mechanisms in Chinese-English bilinguals’ L1 and L2 spoken discourse

Abstract: This article reports an empirical research into the correlation between adult speakers' communication strategic competence and their language proficiency by comparing Chinese-English bilinguals' application of stalling devices in their L1 and L2 spoken discourse. Dörnyei and Kormos' ((1998). Problem-solving mechanisms in L2 communication. Studies in Second Language Acquisition, 20, 349-385) taxonomy of communicative strategies is employed as the analytical framework for the present investigation. The qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…These strategies include inserting hesitation markers (e.g., eh ) or filler words, for which we also found an interaction between chunk length and formality (cf. Tang, 2015, who found an interaction between proficiency and the use of fillers).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These strategies include inserting hesitation markers (e.g., eh ) or filler words, for which we also found an interaction between chunk length and formality (cf. Tang, 2015, who found an interaction between proficiency and the use of fillers).…”
Section: Resultsmentioning
confidence: 99%
“…The speaker-dependent slopes for fillers revealed a more diffuse picture: about half of the speakers used more fillers in informal speech, whereas the other half used more fillers in formal speech. This may be explained by a difference in the function that filler words may have for different speakers (Aijmer, 2004;Götz, 2013;Hasselgren, 2002) or by speakers' individual speaking styles, which they possibly also show in their L1 (Olynyk, d'Anglejan, & Sankoff, 1987;Tang, 2015). For instance, the functions of the filler word like are manifold (e.g., Tagliamonte, 2011) and subtle functional differences in the occurrences of like in our data are conceivable: for some speakers, like may have mainly served pure time-gaining purposes, as in (11), whereas other speakers not only gained time and kept the communication channel open, but also enhanced the informal character of their speech, as in (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…processing has been claimed to be less automatic, yet more resource-demanding than L1 processing (e.g., Rah & Adone, 2010;Saur et al, 2009;Meisel, 2011;Trenkic et al, 2014;Tang, 2015;Reichle et al, 2016). The concept of the less automatic L2 processing applied to the processing of the prepositional phrases in the RC and PRRC structures.…”
Section: Discussion: Differences Between the Participant Groups As Re...mentioning
confidence: 99%
“…Such a result indicated that L2 processing was more resource-demanding than L1 processing. L1 processing's higher degree of automaticity than L2 processing's has been well-attested by a vast body of the L2 processing literature (e.g., Sharifian, 2002;Mueller, 2005;Stowe & Sabourin, 2005;Jin, 2007;Segalowitz & Hulstijn, 2009;Alptekin & Erçetin, 2010;Rah & Adone, 2010;Saur et al, 2009;Meisel, 2011;Trenkic et al, 2014;Tang, 2015;Reichle et al, 2016) Apart from lower automaticity degree of L2 processing, the L2 learners' reading could be impeded and slowed down by Thai-English differences as to the two structures in the test items: RC and PRRC.…”
Section: Criticalmentioning
confidence: 97%